2015
DOI: 10.1590/1678-775720150035
|View full text |Cite
|
Sign up to set email alerts
|

Biological and mechanical properties of an experimental glass-ionomer cement modified by partial replacement of CaO with MgO or ZnO

Abstract: Some weaknesses of conventional glass ionomer cement (GIC) as dental materials, for instance the lack of bioactive potential and poor mechanical properties, remain unsolved. Objective The purpose of this study was to investigate the effects of the partial replacement of CaO with MgO or ZnO on the mechanical and biological properties of the experimental glass ionomer cements.Material and Methods Calcium fluoro-alumino-silicate glass was prepared for an experimental glass ionomer cement by melt quenching techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
(34 reference statements)
2
9
0
3
Order By: Relevance
“…With respect to incorporation of fiber in GIC powders, the aspect ratio (fiber length:diameter), chemical composition, reinforcing fiber fraction, composition of the GIC powder and liquid, and the powder:liquid mixing ratios employed were markedly different for the studies reporting fiber reinforcement of GICs, such that a direct comparison under controlled conditions was not possible. On the other hand, this study confirms that the mean fracture toughness and compressive strength values reported for the commercial GIC without reinforcement are within the range of data previously reported . However, studies have been published reporting higher values of compressive strength for commercial conventional GICs than those obtained in the present study .…”
Section: Discussionsupporting
confidence: 92%
“…With respect to incorporation of fiber in GIC powders, the aspect ratio (fiber length:diameter), chemical composition, reinforcing fiber fraction, composition of the GIC powder and liquid, and the powder:liquid mixing ratios employed were markedly different for the studies reporting fiber reinforcement of GICs, such that a direct comparison under controlled conditions was not possible. On the other hand, this study confirms that the mean fracture toughness and compressive strength values reported for the commercial GIC without reinforcement are within the range of data previously reported . However, studies have been published reporting higher values of compressive strength for commercial conventional GICs than those obtained in the present study .…”
Section: Discussionsupporting
confidence: 92%
“…It has been confirmed in our research, as well as by other researchers, that cement reaction continues after one day, because crosswise bonds are established in the cement matrix [3]. Shiowaza [17] pointed out that cement maturation (acid-base reaction) is continued in the first week that can be seen as an increase in compressive strength and it is then stable for the next 12 months.…”
Section: Discussionsupporting
confidence: 86%
“…Adding Zn has shown to have a stimulating effect on bone formation in in vitro and in vivo conditions, as well as antibacterial activity, similar to silver. Adding MgO increased cell proliferation [3]. Titanium oxide is added because it is chemically stable, biocompatible and has antibacterial properties, and has shown significant activity against Streotococcus mutans in nano-formulation [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations